PENGARUH CELEBRITY ENDORSER PRODUK FAIR N PINK PADA AKUN INSTAGRAM @FAIRNPINKINDONESIA TERHADAP MINAT BELI KONSUMEN - Vintanta K Br S, Emia; ", Rumyeni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Celebrity endorser as a source of advertising or information about the brand and product attributes are fun, convincing and attract the public's attention. There are various products that use celebrity endorser, but beauty products use more. One of them is Fair n Pink. Fair n Pink is a brand of lotion-based skin whitening product that earned the best-seller award in 2017. In marketing its products, Fair n Pink uses celebrity endorsers on instagram. Instagram itself became one of the social media that is very popular, so has a broad range of coverage. Therefore, the use of celebrity endorser of Fair n Pink product in instagram @ fairnpinkindonesia account can generate consumer buying interest. This research uses S-R theory with the purpose of research is to find out how big influence the use of celebrity endorser of Fair n Pink product on account instagram @fairnpinkindonesia to consumer buying interest.The method used is explanative quantitative using random sampling technique and the number of sample as much as 269 respondents. Researches collected data with questionnaires. To find out how big influence between variable X and variable Y, researcher use simple linear regression analysis. To process the test questionnaire data is done by using SPSS program Windows version 23. Based on the result of simple linear regression, obtained regression coefficient value in this research is Y = 5.748 + 0.677 X with 0.000 significance level. The level of significance is smaller than α = 0.05. Which means Ho is rejected and Ha accepted, with the statement that there is no great influence on the use of celebrity endorser of Fair n Pink product on account instagram @fairnpinkindonesia to consumer buying interest. Supporting indicators on the x celebrity endorser variables are divided into four namely, visibility (3.01), credibility (2.96), attraction (2.95) and power (3.03). The indicator of consumer buying interest is divided into four, namely transactional interest (2.86), referential interest (2.80), preferential interest (2.76) and explorative (2.92). Coefficient of determination equal to 0.384. This figure shows that the influence of celebrity endorser of fair n pink product on instagram @ fairnpinkindonesia account on consumer buying interest is 38,4% including weak category.Keyword : Celebrity Endorser, Instagram, Pemasaran, Minat Beli